Study About Social Development and Security: A Recent Perspectives - Chiti, Michael Mulenga (New Innovations in Economics, Business and Management Vol. 9, 2022)
This paper is a study of the Pensions and Insurance Authority (PIA), its regulatory framework, mission, activities and achievement in Zambia. The institution is now a critical component of the country's economy, and the opportunities it presents for the Authority are vast, not only in terms of industrial development but also in terms of maintaining a strong regulatory environment. Insurance is something people buy to prevent themselves from losing money in the event that something awful happens to them or their property. A contract between the insurer and the insured is known as an insurance policy. The company that offers the insurance coverage is known as the insurer. The proposer, also known as the policyholder, is the individual who takes out the insurance.